Estimates Of Genetic Parameters For Body Weight And Shank Length In Aseel Chicken - Pandian, C.; Rajendran, R.; Sundaresan , A.; Omprakash , A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Data on body weight, thigh length and shank length at eighth week from 237 Aseel birds were used for this study. The effects due to hatch and sex were found to be highly significant (P
Keywords: Aseel; shank length; body weight; heritability